Sustainable resource management in next-generation computational constrained networks - Dash, Subhasis (Industry 5. 0 Transformation Applications Series, 2025)
The book provides essential insights into cutting-edge networking technologies that not only enhance performance and efficiency but also address critical sustainability challenges in an increasingly connected world.